Enhanced biodegradation of phenanthrene and anthracene using a microalgal-bacterial consortium - Hoque, Mubasher Zahir; Alqahtani, Abdulrahman; Sankaran, Saravanan; Anand, Deepak; Musa, Musa M.; Nzila, Alexis; Guerriero, Gea; Siddiqui, Khawar Sohail; Ahmad, Irshad (Frontiers in Microbiology, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are chemicals that are released into the environment during activities of the petroleum industry. The bioaccumulation, carcinogenic and mutagenic potential of PAHs necessitates the bioremediation of these contaminants. However, bioremediation of PAHs has a number of limitations including the inability of a single microbe to degrade all of the PAH fraction's environmental constituents. Therefore, a different paradigm, employing microalgal-bacterial consortium (MBC), may be used to effectively remove PAHs contaminants. In this type of interaction, the microalgae and bacteria species in the consortium work together in a way that enhances the overall performance of the MBC. Bacterial species in the consortium provide essential nutrients or growth factors by degrading toxic substances and provide these to microalgae, while the microalgae species provide organic carbon for the bacterial species to grow. For the first time, the ability of Gonium pectorale (G. pectorale) microalgae to break down phenanthrene (PHE) and anthracene (ANT) was investigated. Phenanthrene was shown to be more effectively degraded by G. pectorale (98%) as compared to Bacillus licheniformis (B. licheniformis) 19%. Similarly, G. pectorale has effectively degrade anthracene (98%) as compared with B. licheniformis (45%). The consortia of G. pectorale and B. licheniformis has shown a slight increase in the degradation of PHE (96%) and ANT (99%). Our findings show that B. licheniformis did not inhibit the growth of G. pectorale and in the consortia has effectively eliminated the PAHs from the media. Therefore G. pectorale has a tremendous potential to remove PAHs from the polluted environment. Future research will be conducted to assess Gonium's capacity to eliminate PAHs that exhibit high molar masses than that of PHE and ANT.